Forests for Fuel - Sarma, B. S. K (Indian Forester, 1981)
Mankind will require as much energy in the next 25 years as has been consumed in all of recorded history. All the world reserves of fossil fuels are likely to be exhausted in 5O to 100 years if the present rate of use of fossil fuel continues. A desirable approach to the problem would be to rely more and more on renewable resources like fuelwood (energy plantation) and to conserve the very limited non-renewable fossil fuels for emergency and other specific uses only. There is vast scope of increasing our fuelwood resources through intensive management of existing forests and by creating fuelwood plantations of fast growing tree species on wastelands, village or panchyat lands and other available areas. Tree plantations will also be helpful in environmental conservation and in reducing the hazards of pollution. The supply of such renewable source of fuels will continue as long as planet earth supports life.